Download Analysis II [Lecture notes] by Dirk Ferus PDF

By Dirk Ferus

Show description

Read or Download Analysis II [Lecture notes] PDF

Similar network security books

Security and privacy in mobile social networks

This publication makes a speciality of 3 rising study issues in cellular social networks (MSNs): privacy-preserving profile matching (PPM) protocols, privacy-preserving cooperative facts forwarding (PDF) protocols, and reliable carrier review (TSE) platforms. The PPM is helping clients examine their own profiles with out disclosing the profiles.

Information security management handbook

Thought of the gold-standard reference on info defense, the knowledge defense administration guide offers an authoritative compilation of the basic wisdom, talents, innovations, and instruments required of todays IT safety expert. Now in its 6th version, this 3200 web page, four quantity stand-alone reference is equipped below the CISSP universal physique of information domain names and has been up-to-date every year.

Security for Wireless Ad Hoc Networks

This booklet addresses the issues and brings suggestions to the protection problems with ad-hoc networks. subject matters integrated are danger assaults and vulnerabilities, easy cryptography mechanisms, authentication, safe routing, firewalls, protection coverage administration, and destiny advancements. An teacher aid FTP website is obtainable from the Wiley editorial board

Additional info for Analysis II [Lecture notes]

Sample text

Die Behauptung S(y) =0 y−q lim y→q ist ¨ aquivalent zur Behauptung: ∀ >0 ∃δ>0 ( y − q < δ =⇒ S(y) ≤ y − q ). Sei > 0 und sei δ > 0 dazu wie vorstehend gew¨ahlt. Weil g stetig ist in p, gibt es ein η > 0, so dass x − p < η =⇒ g(x) − g(p) < δ. F¨ ur x − p < η ist dann also S(g(x)) ≤ Weil limx→p R(x) x−p g(x) − g(p) = Dp g(x − p) + R(x) ≤ ( Dp g x − p + R(x) ). = 0, kann man annehmen, dass η > 0 so klein ist, dass R(x)|| <1 x−p f¨ ur 0 < x − p < η. Dann folgt S(g(x)) ≤ ( Dp g Wir haben also zu jedem x − p + x − p ) = ( Dp g + 1) x − p .

Pn ) x3 → f (p1 , p2 , x3 , . . , pn ) ... xn → f (p1 , p2 , p3 , . . , xn ) stetig sind. Man nennt das partielle Stetigkeit, weil man immer nur einen Teil der Variablen - n¨ amlich eine - als variabel betrachtet. Folgt aus partieller Stetigkeit die Stetigkeit? Das ist nicht so: Partielle Stetigkeit impliziert NICHT Stetigkeit. Beispiel 69. Sei f : R2 → R gegeben durch f (0, 0) := 0 und f (x, y) := xy f¨ ur (x, y) = (0, 0). x2 + y 2 F¨ ur λ ∈ R geht n¨ amlich die Folge ( k1 , λk ) gegen (0, 0), aber es ist 1 λ λ f( , ) = 1 2 k k k ( k2 + 32 λ2 k2 ) = λ .

Xn ) − f (p1 , p2 , x3 , . . , xn ) .. + f (p1 , . . , pn−1 , xn ) − f (p1 , . . , pn ). Wir wenden auf jede Zeile den Mittelwertsatz an. f (x) − f (p) = ∂1 f (ξ1 , x2 , . . , xn )(x1 − p1 ) + ∂2 f (p1 , ξ2 , . . , xn )(x2 − p2 ) .. + ∂n f (p1 , . . , pn−1 , ξn )(xn − pn ) 64 mit ξi zwischen xi und pi . Daraus folgt f (x) − f (p) − Fp (x − p) = x−p n xi − p i (∂i f (p1 , . . , ξi , . . , xn ) − ∂i f (p)) x−p i=1 →0 beschr¨ ankt und mit der Stetigkeit der partiellen Ableitungen die Behauptung.

Download PDF sample

Rated 4.62 of 5 – based on 15 votes